Penggunaan Aplikasi Cymath Pada Pembelajaran Aljabar Untuk Meningkatkan Minat Belajar Siswa Kelas 11 - Deni Pratidiana; Ahmad Junaedi (Universitas Mathla'ul Anwar Banten, 2022)
This study aims to use the cymath application to help the difficulties experienced by students in working on Algebra questions in class XI students which causes students to have difficulty understanding Algebraic concepts. The method used in this study is qualitative in the form of a Questionnaire or Questionnaire. The subjects used in this study were eight students of Class 11 with full consideration. Media is a tool used by some teachers to support learning. Technological developments are increasingly rapid and advanced, everyone is expected to be able to understand and understand the use of technology to support learning or support all activities. Teachers and students can take advantage of technology-based learning media, one of which is Cymath. Cymath is an offline and online-based application created by Cymath LLC to assist students in solving math problems that are considered difficult such as Algebra. So that the learning process is interesting and not boring, teachers can teach knowledge and creativity in solving algebra problems in the Cymath application.